2020
DOI: 10.1007/s00402-020-03571-8
|View full text |Cite
|
Sign up to set email alerts
|

A new criterion for assessing Ilizarov treatment outcomes in nonunion of the tibia

Abstract: Introduction The purpose of this study was to assess a population of patients with nonunion of the tibia treated with the Ilizarov method in terms of achieved union rates and maintained union rates, determination of re-fracture factors, with a subsequent comparison of our findings with those reported in the available literature. Materials and methods This study was a retrospective assessment of 102 patients with nonunion of the tibia treated with the Ilizarov method in the period 2008-2015. The assessed parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…Nonunion age & gender distribution: In this study, nonunion was noticed mainly in the age group 30-39 year (33%), next to this was the age group 20-29 years (28%) while its lowest incidence was in the age group 70-79 (2%), this may be related to the small number of old patients who sustained fracture compared to young people who participate in everyday life activities. The mean age was 36.5 years old, which differs from many studies [2][3][4] . The mean age at the start of treatment was 46.7 years, but goes with Bumbaširević 5 were the mean age was 30.4 years.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Nonunion age & gender distribution: In this study, nonunion was noticed mainly in the age group 30-39 year (33%), next to this was the age group 20-29 years (28%) while its lowest incidence was in the age group 70-79 (2%), this may be related to the small number of old patients who sustained fracture compared to young people who participate in everyday life activities. The mean age was 36.5 years old, which differs from many studies [2][3][4] . The mean age at the start of treatment was 46.7 years, but goes with Bumbaširević 5 were the mean age was 30.4 years.…”
Section: Discussioncontrasting
confidence: 70%
“…Gender distribution: It's quite common to find nonunion in males more than females, which was documented strongly in this series by 81% males compared by 19% females out of 84 patients, this may be related to female's life style with all its restricted association as compared to males in our culture. This was supported by the study of Joon-Woo kim 3 (18 patients, 13 men and 5 women), ŁukaszSzelerski 4 in which there was 102 patients (76 men and 26 women), and Bumbaširević 5 (29 males and 1 female), this is may be explained by the life style in our society as women activities outside home is greatly restricted. Fracture pattern: The most common fracture pattern presented in this study was comminuted fracture which was verified in 49 patients (57%), followed by transverse fracture in 25 patients (30%), then oblique fracture in 9 patients (11%) and spiral in one patient (1%), this was related mainly to the severity of the injurious mechanism.…”
Section: Discussionmentioning
confidence: 76%
“…Our results showed that patients older than 45 years (OR0.88, CI0.82-0.94) were more likely to acquire the TGBD than the younger. Via published studies [29][30][31][32], aging is often considered to be accompanied by the loss of bone calcium, and resulting in osteoporosis, which greatly increases the duration of the consolidation stage, the EFT as well as EFI. Another conjecture is that lower extremity bones in the elder are less able to cope with deformity caused by additional forces than young bones, such as bending and rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Cancellous and structural (vascularized) bone grafting, and the induced membrane technique can be combined with the supercutaneous plating technique presented in our paper. Bone transport, a reliable technique to bridge bone defects, is typically performed with an Ilizarov frame [12,14]. A recently published retrospective cohort study presents a 95% maintained union rate in 102 patients treated with the Ilizarov frame for tibia nonunion [14].…”
Section: Discussionmentioning
confidence: 99%
“…Bone transport, a reliable technique to bridge bone defects, is typically performed with an Ilizarov frame [12,14]. A recently published retrospective cohort study presents a 95% maintained union rate in 102 patients treated with the Ilizarov frame for tibia nonunion [14].…”
Section: Discussionmentioning
confidence: 99%